2022
DOI: 10.3390/ijerph192416454
|View full text |Cite
|
Sign up to set email alerts
|

Business Model Innovation Paths of Manufacturing Oriented towards Green Development in Digital Economy

Abstract: China’s manufacturing industry has been confronted with the issue of extensive development with high input, high consumption, and high emissions for a long time, and its green development is the key to reaching carbon neutrality in China. Under the digital economy, business model innovation is the fundamental means of the green development of manufacturing enterprises. Four representative listed companies in China’s manufacturing were selected as typical cases for the case study. Through open, axial, and selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The impact of the digital economy on the circular economy: Studies have shown that the digital economy has the potential to influence China's circular economy, but this impact has not been empirically or quantitatively measured [50][51][52].…”
mentioning
confidence: 99%
“…The impact of the digital economy on the circular economy: Studies have shown that the digital economy has the potential to influence China's circular economy, but this impact has not been empirically or quantitatively measured [50][51][52].…”
mentioning
confidence: 99%
“…A mutually reinforcing coupling relationship exists between the digital economy and green technology innovation. The digital economy has increased the value-added and improved the efficacy of innovation in green technology 32 . Initially, the digital economy alleviates financial limitations for projects affiliated with green technology innovation.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…However, only exploring and analyzing the linear or nonlinear relationship between these antecedent factors and the green transformation of enterprises cannot truly clarify the mechanism through which multiple antecedent factors connect and drive this transformation. Regarding research on the green transformation of manufacturing enterprises, most scholars equate enterprise green technological innovation with enterprise green transformation and choose to use methods such as system dynamics 5 or case studies for research 6 . In fact, enterprise green technological innovation is only one part of enterprise green transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Research on “what combination of factors can improve the level of green transformation of manufacturing enterprises” belongs to a complex causal relationship problem, while configuration thinking focuses on “multiple causes and one result”, which helps to explain multiple concurrent causal complexity problems. The mixed use of fsQCA (fuzzy set qualitative comparative analysis) and NCA (necessary condition analysis) has been widely carried out to study the results of multiple antecedent factors working together 6 . It is an ideal method for analyzing the linkage of various factors, such as technology, the organization, and the environment, on the green transformation of manufacturing enterprises.…”
Section: Introductionmentioning
confidence: 99%